Enhancement of NMDA receptor-mediated currents by light in rat neurones in vitro - Leszkiewicz, Daniel N (Blackwell Science Inc, 2000)
1. N-Methyl-D-aspartate (NMDA) receptor function can be modified by the action of several endogenous and exogenous modulatory processes. In the present study, we report that brief pulses of light potentiate NMDA, but not non-NMDA glutamatergic receptor-mediated whole-cell and single channel currents in rat cortical neurones in vitro. In addition, light also potentiated NMDA receptor-mediated whole-cell responses in isolated rat retinal neurones. 2. Potentiation of NMDA whole-cell currents in cortical neurones was readily observed during and following a brief (< 2 s) exposure of neurones to wavelengths of less than 324 nm of relatively bright light (0·09 μW μm(−2)). In addition, prolonged exposures (> 30 s) to visible wavelengths (> 380 nm) or to attenuated light (1-3 % transmittance of non-attenuated light) were also sufficient to enhance NMDA receptor-mediated responses. 3. The light-induced potentiation of NMDA receptor-mediated currents persisted for several minutes, slowly reversing to control levels with a time constant of approximately 5 min. A subsequent exposure to light could potentiate NMDA receptor-mediated currents for a second time. 4. Light did not alter the apparent affinity of the NMDA receptor for the co-agonists NMDA and glycine. Additionally, potentiation of the NMDA-induced currents was not mediated by a change in the pH sensitivity of the receptor. In excised outside-out membrane patches, the effects of light on NMDA-activated unitary currents were manifested as a twofold increase in channel open frequency without alterations in single channel amplitude or open time. 5. Our results suggest the presence of a light-sensitive moiety within the NMDA receptor, or in a closely associated structure, which affects channel properties. This previously unrecognized form of NMDA receptor modulation may provide a tool for understanding the conformational changes associated with its gating. In addition, it is possible that light may affect NMDA receptor-mediated function or dysfunction in the retina.